PENGARUH KEMAMPUAN KERJA, BUDAYA ORGANISASI, IKLIM ORGANISASI DAN LOYALITAS TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN BARAT - Desni Lubis (Universitas Islam Islam Sumatera Utara, 2020)
There is a significant influence between the ability to work the performance of employees, because according to the results of analysis Thitung T-table (2.966 1.67) at n = 96 with the level of Sifgifikansi 95%. There is a significant influence between organizational culture to employee performance, results of Thitung T-Table analysis (3.220 1.67) at n = 96 with the level of Sifgnifikansi 95%. There is a significant influence between the organizational climate to the employees ' performance, because according to the results of the analysis Thitung T-table (1.984 1.67) at n = 96 with a level of equal 95%. There is a significant influence between loyalty to employee performance, because according to the results of analysis Thitung T-table (8.893 1.67) at n = 96 with the level of exposure to 95%. The value F-count F table (87,303 2.46) with DK pemator 4 and DK Denominator 91 together (multiple) there are positive influence and significant work ability, organizational culture, climate organization Andloyalty to the performance of office employees West Medan Primary Tax service. Thus a proposed hypothesis was received.